Barriers and facilitators: Clinicians' opinions and experiences of telehealth before and after their use of a telehealth platform for child language assessment. Issue 6 (29th August 2021) - Sutherland, Rebecca; Hodge, Antoinette; Chan, Esther; Silove, Natalie
Abstract: Background: Despite emerging evidence of validity and reliability, speech and language therapists' (SLT) uptake of telehealth has been limited and barriers remain to the effective and confident use of this service model. The COVID‐19 pandemic has caused significant disruption to essential health services, including speech and language therapy assessment and intervention, meaning that telehealth must now be considered as part of the suite of service delivery options for all clinicians. Aims: To explore the perceived barriers and facilitators of telehealth among community paediatric SLTs before and after their use of a telehealth platform with an embedded standardised assessment tool. Methods & Procedures: Mixed‐methods questionnaires were developed for this study and completed by SLTs before and after the 3‐month trial of the telehealth platform. A total of 38 SLTs completed the pre‐trial questionnaire and training in the use of telehealth platform (Coviu), including instruction in using a standardised, norm referenced language test as an integrated tool within the Coviu platform. A total of 27 SLTs went on to use the telehealth platform, and 25 of these completed the post‐trial questionnaire on which subsequent qualitative and quantitative analysis was completed. Outcomes & Results: Prior to using the platform, perceived barriers included technology issues, limited clinician experience and concerns around parent acceptance of the service. Potential facilitators included access to appropriate platforms, tools and resources as well as increased clinician confidence with telehealth. Following the trial, barriers to telehealth use continued to include technology barriers, particularly internet stability, and client issues, including suitability for telehealth services. Facilitators for future telehealth use included access to appropriate platforms for telehealth, stable and appropriate internet connectivity, and more extensive telehealth resources for both assessment and intervention for this mode of service delivery. Conclusions & Implications: This study provides insights into the perceptions of the barriers and facilitating factors for telehealth use among community‐based SLTs. This information will be useful in developing strategies to promote uptake and effective and confident use of telehealth as a mode of service delivery beyond the pandemic. What this paper adds: What is already known on the subject: Research about telehealth has shown that it is a reliable and valid way of delivering speech pathology services, yet many clinicians have been wary of its use and uptake of telehealth prior to COVID‐19 had been limited. We wanted to know what SLTs thought about using telehealth before and after participating in a 3‐month trial of a telehealth platform with an embedded formal language assessment. What this study adds to existing knowledge: This study indicates that technology issues including internet stability are a barrier to effective telehealth services, but that appropriate telehealth platforms, resources and experience are facilitators of uptake and successful use of telehealth. What are the potential or actual clinical implications of this work?: This information will be useful in developing strategies to promote uptake and effective and confident use of telehealth as a mode of service delivery for children during and beyond the pandemic, including those isolated by geographical or transport barriers.